2011
DOI: 10.1165/rcmb.2010-0282oc
|View full text |Cite
|
Sign up to set email alerts
|

An Extracellular Signal–Regulated Kinase 2 Survival Pathway Mediates Resistance of Human Mesothelioma Cells to Asbestos-Induced Injury

Abstract: We hypothesized that normal human mesothelial cells acquire resistance to asbestos-induced toxicity via induction of one or more epidermal growth factor receptor (EGFR)-linked survival pathways (phosphoinositol-3-kinase/AKT/mammalian target of rapamycin and extracellular signal-regulated kinase [ERK] 1/2) during simian virus 40 (SV40) transformation and carcinogenesis. Both isolated HKNM-2 mesothelial cells and a telomerase-immortalized mesothelial line (LP9/TERT-1) were more sensitive to crocidolite asbestos … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 45 publications
2
14
0
Order By: Relevance
“…For example, in malignant mesothelioma, asbestos fibers activate the EGFR causing the activation of extracellular signal-regulated kinases (ERK) downstream (15). Similarly, COX-2/PGE2 and its downstream effectors can be regulated independently of EGFR signaling.…”
Section: Malignant Mesothelioma Molecular Targets Involved In Inflammmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in malignant mesothelioma, asbestos fibers activate the EGFR causing the activation of extracellular signal-regulated kinases (ERK) downstream (15). Similarly, COX-2/PGE2 and its downstream effectors can be regulated independently of EGFR signaling.…”
Section: Malignant Mesothelioma Molecular Targets Involved In Inflammmentioning
confidence: 99%
“…Various studies suggest that receptor tyrosine kinase activation participates in the oncogenic progression of nonneoplastic mesothelial progenitor cells to malignant mesothelioma. Asbestos fibers interact with the external domain of the EGFR to trigger dimerization, activation, and increased EGFR mRNA and protein levels in rat and human SV40 immortalized mesothelial cells (15). Upregulated EGFR and resulting tyrosine phosphorylation leads to the activation of downstream mitogen-activated protein kinase (MAPK) signaling pathway associated with proliferation (42) and to the involvement of EGFR activation in mitogenicity and carcinogenesis induced by asbestos (43).…”
Section: Epidermal Growth Factor Receptormentioning
confidence: 99%
“…Although there is a crosstalk between EGFR and COX-2 in carcinogenesis it is important to stress that EGFR and its downstream effectors can be activated independently of COX-2/PGE2. For example, in MM, asbestos fibers activate the EGFR resulting in activation of extracellular signal regulated kinase downstream (Shukla et al, 2011). Similarly, COX-2/PGE2 and its downstream effectors can be regulated independently of EGFR signaling.…”
Section: Molecular Targets Involved In Inflammationmentioning
confidence: 99%
“…Various studies suggest that receptor tyrosine kinase activation participates in the oncogenic progression of non neoplastic mesothelial progenitor cells to malignant mesothelioma. Asbestos fiber interact with the external domain of the EGFR to cause dimerization, activation and increased EGFR mRNA and protein levels in rat and human SV-40 immortalized mesothelial cells (Shukla et al, 2011). Up-regulated EGFR and resulting tyrosine phosphorylation leads to the Ras activation which phosphorylates directly and activates Raf (Rapidly Accelerated Fibrosarcoma).…”
Section: Epidermal Growth Factor Receptormentioning
confidence: 99%
“…Hill et al (2003) reported that amosite asbestos causes pleural inflammation by increased secretion of Intercellular Adhesion Molecule-1 (ICAM-1), Monocyte Chemoattractant Protein-1 (MCP-1) and Macrophage Inhibitory Protein-2 (MIP-2) in pleural lavage fluid as well as in vitro mesothelial cell culture (Hill et al, 2003). Recent studies from our group have also shown that human mesothelial cells acquire resistance to asbestos-induced toxicity via induction of one or more Epidermal Growth Factor Receptor (EGFR)-linked survival pathways (PI3K/AKT/ERK1/2) during Simian Virus 40 (SV40) transformation and carcinogenesis (Shukla et al, 2011). Many cytokines and growth factors are shown to be implicated in asbestos-induced MM pathogenesis including Tumor Necrosis Factor alpha (TNF-α), Transforming Growth Factor Beta (TGF-β), Platelet Derived Growth Factor (PDGF), Insulin like Growth Factor (IGF) (Liu and Klominek, 2004), interleukin-6 (IL-6), interleukin-8 (IL-8) (Galffy et al, 1999), Vascular Endothelial Growth Factor (VEGF) (Strizzi et al, 2001) and Hepatocyte Growth Factor (HGF) (Cacciotti et al, 2001).…”
Section: Introductionmentioning
confidence: 99%